DIFERENSIASI SEMANTIK HADIS, SUNNAH, KHABAR, DAN ATSAR: IMPLIKASI TEORETIS-METODOLOGIS DALAM PEMBELAJARAN KEAGAMAAN DI MADRASAH - Muhammad Roziq Syafi'ul Umam; Ihda Imam Mubarak; Khamidah Ramadhani (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2025)
Understanding the foundational terminology of Hadith science is a fundamental necessity in Islamic education, particularly at the Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA) levels. This study analyzes the conceptual differentiation among the terms Hadith, Sunnah, Khabar, and Athar, along with their core structural elements, and explores their educational relevance. Using a qualitative descriptive library research method, this study examines various academic literatures and classical texts. The findings indicate that while Hadith and Sunnah specifically originate from Prophet Muhammad SAW, Khabar encompasses a broader scope of information, and Athar primarily attributes to the traditions of the Companions and Successors (Tabi'in). The structural elements of Hadith—namely sanad and matan—serve as critical frameworks for verifying authenticity. Integrating these distinctions into the madrasah curriculum is pivotal for fostering critical, scientific, and proportional thinking among students regarding the secondary source of Islamic law, ensuring they practice religion based on methodologically sound foundations.